2006
DOI: 10.1063/1.2234553
|View full text |Cite
|
Sign up to set email alerts
|

Shrinkage of nanocavities in silicon during electron beam irradiation

Abstract: An internal shrinkage of nanocavity in silicon was in situ observed under irradiation of energetic electron on electron transmission microscopy. Because there is no addition of any external materials to cavity site, a predicted nanosize effect on the shrinkage was observed. At the same time, because there is no ion cascade effect as encountered in the previous ion irradiation-induced nanocavity shrinkage experiment, the electron irradiation-induced instability of nanocavity also provides a further more convinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 12 publications
1
33
0
1
Order By: Relevance
“…This is because the existing theories such as the knock-on mechanism were at the first place built on consideration of the nature of equilibrium, symmetry, periodicity, and linearity of bulk crystalline structure or its approximation, whereas the beam (including electron, ion, and photon beams)-induced nanophenomena are intrinsically of non-equilibrium, amorphous, and non-linear nature. The previous research [5,[9][10][11][12] has demonstrated that our proposed nanocurvature or nanosize effect [5,13] and energetic beam-induced athermal activation or nanotime (soft mode and instability of atomic vibration) effect [5,6] could well explain the above beam-induced nanophenomena and widespreadly control the beam-induced structure changes and nanoprocessing of LDNs. Thus, it has been further asserted that both nanocurvature effect and beam-induced athermal activation effect would control as well dynamic behaviors of atom diffusion and evaporation of one-dimensional (1D) nanowire during uniform e-beam irradiation.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…This is because the existing theories such as the knock-on mechanism were at the first place built on consideration of the nature of equilibrium, symmetry, periodicity, and linearity of bulk crystalline structure or its approximation, whereas the beam (including electron, ion, and photon beams)-induced nanophenomena are intrinsically of non-equilibrium, amorphous, and non-linear nature. The previous research [5,[9][10][11][12] has demonstrated that our proposed nanocurvature or nanosize effect [5,13] and energetic beam-induced athermal activation or nanotime (soft mode and instability of atomic vibration) effect [5,6] could well explain the above beam-induced nanophenomena and widespreadly control the beam-induced structure changes and nanoprocessing of LDNs. Thus, it has been further asserted that both nanocurvature effect and beam-induced athermal activation effect would control as well dynamic behaviors of atom diffusion and evaporation of one-dimensional (1D) nanowire during uniform e-beam irradiation.…”
Section: Introductionmentioning
confidence: 72%
“…On the other hand, people normally resort to the existing knock-on mechanism [8] to explain or predict the energetic (ion or electron) beam-induced nanophenomena including beam-induced dynamic atomic defect creation and annihilation and atom transport processes on LDNs. However, it has been demonstrated that knock-on mechanism cannot offer a full explanation for the experimentally observed beam-induced nanophenomena, especially for these such as the plastic flow or wetting of carbon nanotube [9] and amorphous SiO x nanowire [7], or the shrinking nanocavity along with its cavity-near-surface preferential amorphization [5,10,11] as observed earlier in silicon during energetic beam irradiation. This is because the existing theories such as the knock-on mechanism were at the first place built on consideration of the nature of equilibrium, symmetry, periodicity, and linearity of bulk crystalline structure or its approximation, whereas the beam (including electron, ion, and photon beams)-induced nanophenomena are intrinsically of non-equilibrium, amorphous, and non-linear nature.…”
Section: Introductionmentioning
confidence: 97%
“…Actually, even more universally, along with other experiments 14,15,22,23 (also X. F. Zhu et al, manuscripts in preparation or to be submitted), the experiment herein further confirms that the general principle of nanosize effect (i.e., nanocurature effect as specified in this letter and also including low dimensionconfinement effect at nanoscale) and nanotime effect (i.e., energetic beam-induced athermal activation effect or energetic beam induced-atomic vibration instability and soft mode effect as specified in this letter) as predicted in earlier publications [16][17][18] can be extended for elucidation of nanoinstability of LDNs of different types under such irradiations as well as for elucidation of irradiation of other energetic beams such as ion or photon (i.e., laser) beam. …”
Section: -3mentioning
confidence: 99%
“…In fact, our previous work on the energetic beam irradiation-induced structural instabilities and processing of low dimensional nanostructures (LDNs), such as nanocavities in Si [16,[28][29][30][31], carbon nanotubes [32,33] and amorphous SiOx nanowires [22,34], has proven that our proposed nanocurvature effect [16,17] and energetic beam-induced athermal activation effect [16,18] For the nanocurvature effect on a nanowire, we can suppose that, similar to the particle case [16,17], when the diameter of a nanowire reduces down to nanoscale and can be comparable to its atomic bond length, a positive nanocurvature on the highly curved wire surface will become appreciable, as shown in Fig. 3(a).…”
Section: Resultsmentioning
confidence: 99%